Unpredictable Muse: The Ukrainian War and History in Progress. In Putin's Russia, the Past Erupts into the Present - Álvarez, José Maurício Saldanha (Advances in Social Sciences Research Journal, 2022)
We explore the definitions of the history of the present according to Edgar Moran and François Hartog. The present is a script in progress and demonstrates the fluidity of the story. The essay carries out archeology of the Ukrainian war, debating the past of the Ukrainian contenders, Imperial Russia, and the USSR that always needed a defensive accentuation around its borders. It incorporated Ukraine, creating an industrial region and completing its economy despite repression and Russification. The dissolution of the USSR gave rise to independent countries such as Georgia and Ukraine, supported by the US and NATO. The essay discusses the Ukrainian war without demonizing the contenders by explaining Russian leader Putin's fascination for his country's history. The past that emerges is archaic, demonstrating that Putin wants to control history. Consolidating its nationalist positions rescues the greatness of the Russian Empire, of the extinct USSR, reaffirming its country as a world power in the present. US and NATO foreign policy compromised with the USSR's military actions until the Soviet invasion of Afghanistan. The American government supported the rebels as it does in Ukraine and detached his identity from the Russian past by joining the West. The chapter concludes by showing the time of conflict from the perspective of Giorgio Agamben and Heidegger as the moment of kairós when taken war decisions.